Two channels of scattering of Hubbard chain electrons with spin and orbital interactions (exact results) - Zhuravlyov, A.F. (Вопросы атомной науки и техники, 2001)
A simple way to determine the channel of scattering of the Hubbard chain electrons with additional quantum number, which means the orbital or band characteristic, is demonstrated on the integrable 1D modified Hubbard model. Exact solutions are obtained for each scattering channel of the electrons. The preferable channel is determined by means of numerical calculations of the ground-state energies and comparison its values. The dependence of the scattering matrices on the parameters of Coulomb, orbital (band), and spin interactions gives the possibility to present the properties of the system considered in different ranges (reasonable in physics sense) of parameters which correspond to the electron coupling. The ratio between magnetic susceptibility and heat capacity of the model is presented.